Efficacy of baricitinib in patients with moderate-to-severe rheumatoid arthritis with 3 years of treatment: results from a long-term study . (17th November 2020) - Smolen, Josef S; Xie, Li; Jia, Bochao; Taylor, Peter C; Burmester, Gerd; Tanaka, Yoshiya; Elias, Ayesha; Cardoso, Anabela; Ortmann, Rob; Walls, Chad; Dougados, Maxime
Abstract: Objective: To evaluate the long-term efficacy of once-daily baricitinib 4 mg in patients with active RA who were either naïve to DMARDs or who had inadequate response (IR) to MTX. Methods: Analyses of data from two completed 52-week, phase III studies, RA-BEGIN (DMARD-naïve) and RA-BEAM (MTX-IR), and one ongoing long-term extension (LTE) study (RA-BEYOND) were performed (148 total weeks). At week 52, DMARD-naïve patients treated with MTX monotherapy or baricitinib 4 mg+MTX in RA-BEGIN were switched to open-label baricitinib 4 mg monotherapy; MTX-IR patients treated with adalimumab (+MTX) in RA-BEAM were switched to open-label baricitinib 4 mg (+MTX) in the LTE. Patients who received placebo (+MTX) were switched to baricitinib 4 mg (+MTX) at week 24. Low disease activity (LDA) [Simple Disease Activity Index (SDAI) ≤11], clinical remission (SDAI ≤ 3.3), and physical functioning [Health Assessment Questionnaire Disability Index (HAQ-DI) ≤ 0.5] were assessed. Data were assessed using a non-responder imputation. Results: At week 148, SDAI LDA was achieved in up to 61% of DMARD-naïve patients and 59% of MTX-IR patients initially treated with baricitinib, and SDAI remission was achieved in up to 34% of DMARD-naïve patients and 24% of MTX-IR patients; HAQ-DI ≤ 0.5 was reached in up to 48% of DMARD-naïve patients and 38% of MTX-IR patients initially treated with baricitinib. Over 148 weeks, 3.6% and 10.7% of MTX-IR patients discontinued across treatment groups due to lack of efficacy or due to adverse events, respectively; discontinuation rates were similar in the DMARD-naïve population. Conclusion: Treatment with baricitinib 4 mg demonstrated efficacy for up to 3 years and was well tolerated.